Deixis Analysis on The Halsey’s Song Lyrics “Manic” Album - Sufil Lailiyah (Universitas PGRI Yogyakarta, 2023)
Deixis is important to help the listener or addressee distinguish between what the speaker says and what is intended. It is possible that the listener might misinterpret a reference in vague utterance. The meaning of a sentence or utterance becomes understandable if the addressee knows who, when, and where it is spoken. In this study, researcher examines the types and meaning of deixis used in Halsey's songwriting lyrics. The study involves qualitative data analysis. The data are obtained through listening to song lyrics, understanding lyrics, looking for deixis, and finally noting down the data. After obtaining the data, the data are analyzed in some ways; identifying the types of deixis in Halsey’s song lyrics “manic” album, describing the meaning of deixis words that found in that song lyrics, and concluding the result of the data analysis. The result of the study showed that there are 130 data of deixis. They are divided into 105 data of person deixis, 5 data of place deixis, 1 datum of time deixis, 17 data of discourse deixis, and 2 data of social deixis in Halsey’s song lyric album. Person deixis was investigated as the most dominant type of deixis in the lyrics. All deixis had their meanings based on the situations of the song.